Anthracene‐Based Colloidal Polymer Nanoparticles: Their Photochemical Ligation and Waterborne Coating Applications. (7th May 2018) - Chattopadhyay, Subrata; Van Damme, Jonas; van den Berg, Otto; Du Prez, Filip
Abstract: In the current work, a linear polymer, with anthracene moieties in the side chain, is prepared via step‐growth polymerization using epoxide‐amine ring opening reaction. The polymer is dispersed in water to form physically crosslinked nanoparticles (NPs), which are formed by π–π stacking of anthracene moieties. Later, the NPs are crosslinked using UV irradiation, where the anthracene units in the core are simply dimerized and crosslinked the individual chain. In this process, no significant interparticle crosslinking is observed. The higher structural integrity of the chemically crosslinked Nps is revelled via a simple swelling test. The colloidal solution is used to coat glass and silica surfaces homogeneously, which enhances the surface roughness significantly as revealed by atomic force microscope and contact angle measurements. Abstract : A strategy for the preparation of physically crosslinked nanoparticles, using a newly synthesized anthracene‐based polymer, is developed. The core of the nanoparticle can be easily chemically crosslinked on demand, using an additive free photochemical reaction. Different surfaces are coated using the colloidal solution, which is increasing both their surface roughness and hydrophobicity.